The Effect of Dates on Hypertension in Elderly People in Sei Deras Village - Sumi Lestari; Andria (International Journal of Health Engineering and Technology, 2025)
Elderly is someone aged 45-59 years called pre-elderly, 60-69 years old is young elderly, 70-79 years old is middle elderly, and 80-89 is old elderly. Where the aging process is a life cycle marked by stages of decline in various organ functions in the body which is marked by the body's susceptibility to various disease attacks. One of the diseases that is often experienced by the elderly is hypertension. Magnesium, potassium falvonoit are found in abundance in fruits, One of the fruits that can be used as an alternative natural treatment for hypertension is dates, This study uses a pre-experimental method with a research one group pre test and post test, design using an observation sheet tool and the population of this study was 13 people with a sample of 10 elderly people, the average systolic blood pressure of pretest respondents was 150.70 mmHg. Diastolic pre-test is 90.80 mmHg, Average blood pressure Post-test is 126.60 mmHg, diastolic post-test is 79.30 mmHg Based on the results of the T-dependent statistical test analysis for the difference in systolic blood pressure before and after giving dates, the p value is obtained = 0.000, this means p <0.05. Ho is rejected, this shows that dates have a significant effect on systolic blood pressure. For the difference in diastolic blood pressure before and after giving dates, the p value is 0.002, this means p <0.05, Ho is rejected, this shows that dates have a significant effect on diastolic blood pressure.